Utilization of cement deep mixing pile for soft soil foundation: a malaysian case study - Xue, Zhiguo; Zhang, Wenfeng; Zhao, Xiaobo; Meng, Fanjie; Qin, Fang; Xiao, Guliang; Nie, Zhenyu; Chen, Jiantao (Frontiers in Materials, 2024)
Cement deep mixing piles, as representatives of deep mixing technology, are mature and widely applied. However, effective application cases of cement deep mixing piles are relatively scarce in countries like Malaysia in Southeast Asia. In this paper, the application of cement deep mixing pile reinforcement in Malaysia is presented. Solidifying material was selected for deep mixing piles based on the soil conditions using unconfined compressive strength (UCS) tests. The relationship between the strength of deep mixing piles on-site and soil properties (type, organic matter content, and ion content) was analyzed. And a quality evaluation of the deep mixing piles in the project is conducted based on Kolmogorov-Smirnov (K-S) tests and relevant standards. Results show that fly ash cement is suitable as a solidifying agent for acidic soil layers containing organic matter in the local area. The strength of piles is significantly related to the soil condition. The UCS of cement mixing piles in silty clay and peat soils is smaller than clay. The overall correlation between organic matter content in the soil and UCS is negative, particularly when the organic matter content ranges from 10% to 14%, resulting in a significant drop in UCS. The bilateral significance probability is greater than 0.05 in K-S test, indicating that the UCS results in the projectconform to a normal distribution. Additionally, the evaluation of the overall quality of the mixing piles aligns with the requirements in the Japanese standard “Manual of Deep Mixing Construction Technology for Harbors and Airports” and the Chinese standard “Technical Code for Building Foundation Detection”.